MULTIMODAL CONTAINER TRANSPORTATION OF GOODS AS A TOOL FOR SUSTAINABLE DEVELOPMENT OF THE TRANSPORT SYSTEM OF UKRAINE - Sokolova, Olena (Science-based technologies, 2021)
The article analyzes the dynamics and structure of freight transport in Ukraine. It has been established that the level of containerization of cargo flows in Ukraine is an insignificant part in comparison with the EU countries. In order to optimally realize the trade, economic and transit potential of the country, it is the multimodal schemes for the transportation of goods that are of great importance, which ensure a high level of reliability, safety and quality of service. It was found that one of the key transport problems at the global level is the reduction of pollutant emissions into the air. Investigated international environmental requirements and measures to reduce the negative impact of transport on the environment. To achieve the established environmental goals and indicators, Ukraine needs to intensify work on the development of an energy efficient and environmentally sustainable transport system, based on the development of multimodal container transport with the involvement of "clean" modes of transport, namely rail. The conceptual provisions for the formation of an environmentally sustainable system of multimodal container transport (SMMCT) in Ukraine have been developed. The proposed SMMCT of Ukraine is a set of effective principles, methods, mechanisms and other tools for sustainable development, allows for optimal management of organizational and technological processes and infrastructure facilities for multimodal container transportation. In order to form an environmentally sustainable SMMCT of Ukraine, trends in the development of road and rail transport in terms of cargo turnover in the structure of the system for the supply of imported goods to domestic markets have been determined. It is proved that the development of container rail transportation allows to obtain an environmental effect as a result of reducing CO2 emissions into the air